Powering Change: A Methodology for Prioritizing Locations When Burying Power Lines to Minimize Wildfire Damage in Communities - Malhotra, Tara (International Journal of Environmental Sciences, 2025)
Purpose: Overhead power lines can spark and cause extremely devastating wildfires. This has happened with power lines from utility companies such as Pacific Gas and Electric Company (PG&E), Southern California Edison (SCE), and San Diego Gas and Electric (SDG&E). One method of preventing widespread wildfires is to bury power lines underground. When planning to bury lines, utility companies must evaluate where power lines should be buried to minimize collateral damage from wildfires while enhancing infrastructure strength. This research paper advances a novel methodology for identifying and prioritizing the ideal locations for underground power lines. Methodology: Using California as a case study, I examine low, medium, and high wildfire risk locations in PG&E’s, SCE’s, and SDG&E’s jurisdictions. I determine which locations should be prioritized regarding the construction of underground lines by looking at the following factors in geographic information system (GIS) mapping: overhead power lines, critical infrastructure, past wildfire activity, population density, disadvantaged communities, and thermal hotspots. Findings: The results reveal the importance of considering variables like population and infrastructure density when mitigating wildfire risk with underground power lines, expanding the evaluation beyond typical factors like dry vegetation. Unique Contribution to Theory, Practice and Policy: My methodology can be used by utility companies in order to conserve resources and time due to the structured approach. Doing so will also expedite the process of burying power lines which minimizes the impact of wildfires caused by overhead lines.